Perekonomian Indonesia ditinjau dari financial technology menurut perspektif Islam - Ruslan, Mukhammad; Hidayati, Nur; Asiyah, Siti (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Economic development in Indonesia with technological advances has a significant impact. Innovation and new technological breakthroughs today in the financial sector using Fintech or financial technology. Fintech initially only existed in the conventional financial system, but along with the times, fintech has now entered the Islamic financial system. The purpose of this study is to analyze fintech in the economy in Indonesia through an Islamic perspective. The type of research used is to use literature studies obtained from various sources. This research is descriptive and qualitative. The data used is secondary data. The data collection technique is to use literature review to examine the theoretical basis related to fintech concepts and mechanisms that are currently developing rapidly in accordance with the principles of Islamic law. As well as knowledge of the development of sharia fintech as the main basis for building correlations between practice and theory based on Islamic perspectives. This research produces Fintech in an Islamic perspective, offering alternative choices to people who use financial technology services, especially for people who want to avoid the trap of usury, because the fact that occurs almost entirely contains elements of usury. However, muamalah is not only important in terms of economic value but must also be of worship value so that muamalah activities become a blessing of participation.